Production of monoclonal antibody to acaricide dicofol and its derivatives - Hongsibsong S. (2014)
In Thailand detection of acaricide dicofol residues has been sporadically performed due to the limitation of analytical techniques. Conventional analytical methods for detecting dicofol residues most often use chromatographic-based techniques. Our ultimate aim is to develop an alternative method for rapidly analyzing dicofol residues in vegetables and fruit samples. Here we report the production of monoclonal antibodies specific to dicofol and its derivatives. Hapten-protein carriers were prepared by linking succinic anhydride to dichlorobenzhydrol (DCBH), which was then conjugated to bovine serum albumin (BSA) and oval albumin (OVA). DCBH-BSA conjugate was used as immunogen while DCBH-OVA conjugate was used as capture antigen for competitive inhibition assay. Female BALB/c mice were immunized with DCBH-BSA conjugate subcutaneously, and antibody (Ab) level was determined 2 weeks after the last immunization. Spleen cells producing high titer antibody were isolated and fused with myeloma cells of P3.X6.Ag8.653. After limiting dilutions, antibody produced by one clone had high affinity, which was found to be of IgG1 with κ light chain. Specificity and inhibition concentrations of the monoclonal antibody (MAb) were determined by competitive indirect ELISA with dicofol, and its 50% (IC50) was 0.28 μg/mL. Working ranges of the developed immunoassay were from 0.07 to 25 μg/mL. Hence, the prepared MAb will be able to be applied for immunoassay development for detecting dicifol residue in vegetables and fruits far below the maximum residue limit such that 5 g of fruits and berries can be detected below 0.1 mg/kg. © Copyright 2010, Mary Ann Liebert, Inc. 2010.